2004
DOI: 10.1159/000076651
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Early Postoperative Enteral Nutrients versus Chow on Colonic Anastomotic Healing in Normal Animals

Abstract: We aimed to clarify the effects of different enteral nutrients (normal chow, complete balanced nutrition, elemental nutrition enriched with glutamine, immune-enhancing diet and fiber) on colonic anastomotic healing in the stress-free metabolic state. The study was carried out with 50 male Balb-C mice in five groups of 10 animals each. After transverse colon anastomosis, animals were fed with early enteral nutrients using normal chow (group 1), Ensure® (group 2), Alitraq® (group 3), Impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
0
10
0
4
Order By: Relevance
“…Some of these factors include tenuous blood supply, high bacterial presence, and increased intraluminal pressure because of colonic contents. [5][6][7]18,19 Investigators have used various experimental models to improve colonic anastomotic healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these factors include tenuous blood supply, high bacterial presence, and increased intraluminal pressure because of colonic contents. [5][6][7]18,19 Investigators have used various experimental models to improve colonic anastomotic healing.…”
Section: Discussionmentioning
confidence: 99%
“…4 Many factors have been proposed to affect colonic healing. [5][6][7] Various authors have described impaired colonic healing and increased anastomotic leakage rates after short-term and long-term cortisone treatment. [8][9][10] Insulin-like growth factor I (IGF-I) is a peptide hormone structurally related to insulin, which has pleotrophic effects on cell growth and metabolism.…”
mentioning
confidence: 99%
“…In an animal model, Moss et al (94) demonstrated that early enteral feeding doubled the bursting pressure of the colorectal anastomosis, with the anastomoses containing significantly higher concentration of collagen and collagen precursors than those of the unfed controls. Multiple experimental studies have demonstrated that early EN following bowel surgery is associated with improved wound healing, greater wound strength, and higher wound hydroxyproline and collagen accumulation (95)(96)(97)(98)(99)(100). This may explain the lower risk of anatomic leaks and fistulas in bowel surgery patients who receive early enteral as opposed to delayed feeding or PN (5,9,101).…”
Section: Myth No 8: En Is Contraindicated Following Gi Surgerymentioning
confidence: 99%
“…If adhesions were present they were not dissected but harvested together with the anastomos since dissection could diminish the strength of the anastomos 8 . A silicon tube was inserted into the ileum, while the colonic side was ligated at the end.…”
Section: Adhesion Studymentioning
confidence: 99%